A systematic literature review: The effects of surface roughness on the wettability and formation of intermetallic compound layers in lead-free solder joints. (November 2022) - Ismail, N.; Atiqah, A.; Jalar, A.; Bakar, M.A.; Rahim, R.A.A.; Ismail, A.G.; Hamzah, A.A.; Keng, L.K.
Abstract: This study reviews the existing research on the effects of surface roughness on the wettability and intermetallic compound (IMC) layer formation in lead-free solder joints. The studies are reviewed scientifically to highlight the most significant work undertaken on the surface roughness of lead-free solder alloys. A total of 171 studies were found in the Scopus, Google Scholar, and Dimensions databases. After the search had been limited to articles and review papers in this literature review, the databases produced only 114 results. When searching specifically for the wettability properties and IMC layer of lead-free solder materials, only 41 results were returned. After analysis using Microsoft Excel, the studies were classified according to the process followed. Most previous studies focused on the soldering process and lead-free solder materials. The latest surface roughness properties of lead-free materials must be reviewed to demonstrate the correlation between the soldering process and different factors. The studies were found to emphasize the effects of surface roughness on the wettability and IMC layer formation of lead-free solder materials. Moreover, the current study also identified a new post-treatment approach involving additives or the reinforcement of lead-free solder materials. While more future work can be conducted on the post-treatment of the alloying element to enhance the properties of lead-free solder material.